Processes in management of food traceability: A cross-case study between Spain and Sweden - Mayo Castillo, Pablo (My University, 2025)
In a world where consumers demand greater transparency and safety in the food they eat, traceability has become a critical part of modern food systems. Regulations across the European Union have made food and fish traceability a legal requirement, but the way these rules are implemented can differ significantly from one country to another. This thesis explores how public authorities in Spain and Sweden manage traceability through administrative and logistic processes, providing a practical perspective on how theory and legislation are translated into real action. The research adopts a qualitative case study approach, based on interviews with representatives from government agencies responsible for traceability enforcement in both countries. The aim is to understand how inspections, documentation, coordination, and control mechanisms are used in practice, and how these differ between a centralized model like Sweden’s and a decentralized structure like Spain’s. The study also reflects on the human side of traceability; how communication, trust, and professional judgment play key roles in ensuring that systems work as intended. Findings reveal both common challenges and contrasting approaches. The study highlights that successful traceability depends not only on strong regulations and modern tools, but also on the people and institutions behind them. By offering a comparative and grounded view, this research contributes to a deeper understanding of how food safety is managed in practice, and how future improvements can be guided by both structure and experience.
Keywords: Traceability; Regulation; Logistics; Compliance; Authorities; Inspection; Governance; Coordination; Transparency; Enforcement; Spårbarhet; reglering; logistik; efterlevnad; myndigheter; inspektion; styrning; samordning; ransparens; verkställighet